Artomandin, a new xanthone from Artocarpus kemando (Moraceae). - Ee, Gwendoline Cheng Lian; Siow, Hwa Teo; Rahmani, Mawardi; Chan, Kiang Lim; Yang, Mooi Lim; Go, Rusea (Taylor & Francis, 2011)
A new furanodihydrobenzoxanthone, artomandin (1), together with three other flavonoid derivatives, artoindonesianin C (2), artonol B (3), and artochamin A (4), as well as β-sitosterol (5) were isolated from the stem bark of Artocarpus kemando. The structures of these compounds were determined on the basis of spectral evidence. All of these compounds displayed inhibition effects to a very susceptible degree in cancer cell line tests. Compound 1 also exhibited significant antioxidant capacity in the free radical 1,1-diphenyl-2-picrylhydrazyl tests.